Analisis-Kritis Tafsir Maqashidi atas Penafsiran Poligini Muhammad Syahrur - Musfiqoh, Nailatul; Hamidah, Tysa Nur; Nauval, Mukhammad Hubbab; Naqiah, Naqiyah (Program Studi Ilmu Al-Qur`an dan Tafsir, Fakultas Ushuluddin, UIN Sunan Kudus, 2022)
Maqashidi's Critical Analysis of the Polygynous Interpretation of Muhammad Syahrur. The issue of polygyny is still a matter of controversy both among the general public and classical to contemporary Muslim scholars. Syahrur as one of the contemporary Islamic thinkers also contributed by presenting a new perspective through his limit theory (had al-adna and had al-a'la). This study aims to analyze Syahrur's thoughts on polygyny using the maqashidi interpretation paradigm. This study will use the maqashidi interpretation paradigm as the philosophical basis for the interpretation of the Qur'an (maqashidi as philosophy and as critic) to review the extent to which Syahrur's interpretation is compatible with the principles of maqashid as-syari'ah and maqashid al-Quran. The results of This study shows that the polygynous verse, in Syahrur's view, is basically a solution to the social problems of humanity that arose in the context of Arab society at the time of the Prophet.Through the analysis of the maqashidi interpretation paradigm the author concludes that Syahrur's interpretation of the polygynous verse is in accordance with the values of maqashid as-Shari'ah values such as hifz ad-din, hifz an-nafs, and hifz an nasl. Likewise with maqashid al-Quran values such as justice, humanity, freedom, and the value of responsibility. Syahrur did not respect other maqashidi values such as hifz an nasl and the value of justice.